Metode Behavioris dan Humanis Tahfiz Al-Qur’an Anak Usia Sekolah Dasar - Azis, Donny Khoirul; Maknun, Moch Lukluil; Muntakhib, Ahmad; Noviani, Nur Laili (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The problem of Qur'an tahfiz for elementary school-age children requires a solution. This age has different competencies from school age above and adults so it requires different methods. This study presents tahfiz Qur'an methods for elementary school children, guidance patterns, supporting and inhibiting factors, and then looks for ideal methods and guidance formulations. This explanatory case study took the subjects of twenty-two students from two selected pesantren, namely Pesantren Yanbu'ul Qur'an Kebumen which applies behavioristic pattern and Pesantren An-Nur Bantul with humanistic pattern. Data were collected through observation, interviews, documentation, tested through data triangulation, then utilizing the Miles & Huberman interactive model analysis. With the goal of formulating an ideal Qur'an tahfiz method for children, this study is preceded by presenting the findings of common methods used in Qur'an tahfiz, guidance patterns, and supporting and inhibiting factors. In the end, the ideal tahfiz method for children, besides creating a structured system and providing a conducive learning environment, is one that pays more attention to the characteristics of students (humanist).